2016
DOI: 10.7717/peerj.1694
|View full text |Cite
|
Sign up to set email alerts
|

Broad-scale sampling of primary freshwater fish populations reveals the role of intrinsic traits, inter-basin connectivity, drainage area and latitude on shaping contemporary patterns of genetic diversity

Abstract: Background. Worldwide predictions suggest that up to 75% of the freshwater fish species occurring in rivers with reduced discharge could be extinct by 2070 due to the combined effect of climate change and water abstraction. The Mediterranean region is considered to be a hotspot of freshwater fish diversity but also one of the regions where the effects of climate change will be more severe. Iberian cyprinids are currently highly endangered, with over 68% of the species raising some level of conservation concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 76 publications
3
25
0
Order By: Relevance
“…In contrast, some large rivers, such as Guadiana and Guadalete, showed surprisingly low genetic diversity values in comparison with other large basins, as Guadalquivir Basin, which could be consequence of recent founder effects, as supported by the estimated divergence times. This lack of correlation between diversity indices and basin size has already been reported for other Iberian cyprinid fishes (Perea & Doadrio, ; Sousa‐Santos et al., ).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In contrast, some large rivers, such as Guadiana and Guadalete, showed surprisingly low genetic diversity values in comparison with other large basins, as Guadalquivir Basin, which could be consequence of recent founder effects, as supported by the estimated divergence times. This lack of correlation between diversity indices and basin size has already been reported for other Iberian cyprinid fishes (Perea & Doadrio, ; Sousa‐Santos et al., ).…”
Section: Discussionsupporting
confidence: 71%
“…Other previous studies dealing with the genetic diversity of L. sclateri in Portuguese basins showed that the haplotype diversity was lower in comparison with other cyprinid species. In addition, the highest diversity was found in Guadiana River, the largest one considered in the study (Sousa-Santos et al, 2016). Previous genetic studies did not include many of the southern Spanish populations that comprise most of the distribution range of the species (Gante et al, 2009).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, our preliminary conclusion is that the extinction of Penyscola was too abrupt to leave any genetic footprint. This scenario somehow resembles the case of the high nuclear (and mitochondrial) diversities critically reported for the endangered Iberian fish Anaecypris hispanica and attributed to recent fragmentation and decline of its populations [89, 93]. Overall, the loss of Penyscola did not substantially affect to the nuclear and mitochondrial diversity present in our 17 sampled sites.…”
Section: Discussionsupporting
confidence: 85%
“…This kind of watershed experiences a predictable annual cycle of autumn-winter floods and extended summer droughts. These changes result in a series of disconnected ponds during the dry season and affect biological community traits [88, 89]. This is illustrated by the earlier breeding season of G .…”
Section: Discussionmentioning
confidence: 99%